Estratificação do risco de arritmias em pacientes com fenótipo eletrocardiográfico de Brugada tipo I através do teste ergométrico - Mina, Camila Pinto Cavalcante (2024)
Introduction: Brugada syndrome (SB) is a channelopathy of genetic origin with a global prevalence of 0.05%, accounting for 4% of all sudden death (MS) events. Implantable cardioverter defibrillators (ICDs) are the only recommended therapy for individuals with BS who are survivors of cardiac arrest. However, defining patients with BS who would potentially benefit from ICD implantation in primary prevention remains a challenging and controversial topic. In this context, the exercise test (ET) has shown some relevance in the prognostic stratification of these patients. Objectives: To evaluate clinical and electrocardiographic characteristics of patients with Brugada type I phenotype during ET in comparison to the control group, and investigate possible associations between the findings described in the literature (induction of ventricular arrhythmia, elevation of the J point and exacerbated decrease in heart rate-HR in post-exertion phase) with the presence of spontaneous arrhythmic events. Methodology: this is an observational case-control study. Between 2021 and 2023, patients with Brugada type I electrocardiographic phenotype with or without a history of arrhythmic events were recruited (spontaneous ventricular fibrillation-VF/ventricular tachycardia-VT, recovered cardiac arrest, syncope, or appropriate ICD shock). Patients responded to a data collection questionnaire and performed ET, in which, in addition to conventional analyses, the behavior of the J point was observed in modified V1 and V2 leads, arranged in the second intercostal space, in the post-exertion phase. A control group matched by sex and age was recruited. For comparison purposes, patients with BS were separated into two groups: BS patients with arrhythmic events (BWE) and BS participants with no arrhythmic event (BWNE). Results: A total of 36 patients with BS were recruited, predominantly male (86.1%), with mean age of 48.1 ± 10.1 years. Atrial fibrillation was found in 13.8% of patients (predominance of the paroxysmal form), 56.3% were asymptomatic, and 63.8% had an ICD. During ET, patients with BS did not report cardiovascular symptoms and demonstrated cardiorespiratory fitness similar to the control group. Three patients with BS presented ventricular arrhythmias (polymorphic and monomorphic ventricular extrasystoles, isolated and paired), with no episodes of VF/VT. Even though patients using negative chronotropic drugs were excluded, patients in the BWE group had a lower capacity to increase HR at peak effort and a greater proportional drop in the recovery phase (p<0.001). There was no difference in the magnitude of J-point elevation between patients in the BWE and BWNE groups. Conclusion: The present study suggests that the ET may be safe among patients with BS, and that it may be helpful to identify prognostic characteristics in this population.